SAT0376 Hepatic osteodystrophy in patients with chronic autoimmune cholangiopathies: Primary biliary cirrhosis, primary sclerosing cholangitis and autoimmune cholangitis. (23rd January 2014) - Ruiz, A.; María, T.; García-Buey, L.; Moreno, R.; Vega, G.; Camacho, D.; Castañeda, S.; Vicente, E.
Abstract : Background: Hepatic osteodystrophy is a frequent complication of chronic hepatopathies, although its knowledge in immune mediated chronic liver disease as primary biliary cirrhosis (PBC), primary sclerosing cholangitis (PSC) and autoimmune cholangitis (AIC) is scarce. Objectives: 1. To study the prevalence of fragility fractures, osteoporosis (OP) and osteopenia and its association with the severity of hepatopathy (Child-Pugh, MELD) and the hepatic fibrosis stage (FibroScan®) in this population. 2. To assess whether a T-score <-1.5 could be a cut-off point that identifies an increased risk of fracture in these patients. 3. To estimate their absolute risk of fracture using the FRAX® tool. 4. To analyze if clinical practice is in compliance with treatment recommendations of OP proposed by the European Association for the Study of the Liver (EASL) and FRAX guidelines. Methods: Preliminary cross-sectional observational study of bone density and fragility fractures in patients with PBC, PSC and AIC attended at our hospital during last year. Among 107 eligible patients, 45 (53%) fulfilled the inclusion criteria of having bone mineral density (BMD) evaluation by dual X-ray absorptiometry (DXA) using an Hologic QDR 4500-Elite® densitometer at lumbar spine and total hip. The protocol included a questionnaire for sociodemographic variables, fractures and OP risk factors. Results: Mean age was 57 yrs (range: 28-81 yrs) and 84% were women (31% postmenopausal). Disease distribution was: 89% PBC, 6.7% AIC and 4.4% PSC. BMD assessment is shown in Table. Prevalence of global fractures was 38% (non vertebral 38% and vertebral 7%). We found an association between vertebral fractures and serum bilirubin >1.3 mg/dL, serum albumin <3.4 g/dL and F4 stage by FibroScan® (p<0.05), which remained significant after adjustment for possible confusion factors. Likewise, hip fracture was associated with early menopause, F3 stage and lumbar spine and femoral neck OP (p<0.05). A T-score <-1.5 in lumbar spine (58.5% [95% CI: 42-75]) and femoral neck (53% [95% CI: 48-69]) did not correlate with prevalent fractures. The mean 10 yrs absolute risk of fractures obtained by FRAX® was 6% for major fractures and 2% for hip fracture. Doctors younger than 40 yrs had ordered DXA more frequently (68%) than doctors over 40 yrs (46), p=0.05. OP prevention and treatment was in compliance with EASL guidelines in 58% of eligible patients. FRAX® recommendations identified 22% patients eligible for OP treatment whereas EASL guidelines identified 58% (p=0.001). Conclusions: Prevalence of OP in cholangiopathies was greater than described for general Spanish population of the same age. A T-score <-1.5 was not associated with increased fracture risk in our patients. FRAX® identified less eligible patients for OP treatment than EASL guidelines. There is still a high prevalence of undertreatment of bone loss in patients with cholangiopathies. Disclosure of Interest: None Declared